EN TORNO A LAS RELACIONES INTERNACIONALES - Jaguande DÁnjoy, Alfonso (2019)
In this article the author proposes that the fundamental concern of international relations should focus in designing and constructing an alternative model where justice prevails for the international system to develop in peace. As we know, international relations have their origin in the field of political science when disaggregating from the latter it focused on the study of states in relation to other units of the international system.